Acutely Rising Temperature Reduces Photosynthetic Capacity of Phytoplankton Assemblages in Tropical Oceans: A Large-Scale Investigation - Mai, Guangming; Liu, Jihua; Xia, Xiaomin; Pang, Xinyue; Li, Binkai; Yu, Linghui; Tan, Yehui; Song, Xingyu; Li, Gang (Frontiers in Marine Science, 2021)
Climate changes interacting with human activities are raising the temperature in global oceans. To explore physiological responses of in situ phytoplankton assemblages to increasing temperatures, we conducted a shipboard experiment in tropical regions of the eastern Indian Ocean, Java Sea, and southern South China Sea. Throughout the surveyed areas, phytoplankton biomass (Chl a) ranged from 0.09 to 0.86 μg L-1 (median, 0.22 μg L-1) in surface and from 0.30 to 0.99 μg L-1 (median, 0.50 μg L-1) in maximal chlorophyll layer (DCM), respectively. Picophytoplankton that occupied 27%-89% (79%) and 83%-92% (88%) of total Chl a in surface and DCM layers, ranged from 0.32×104 to 23.10×104 cells mL-1 (3.69×104 cells mL-1) and from 7.44×104 to 25.70×104 cells mL-1 (12.60×104 cells mL-1), respectively. Synechococcus took up 30%-97% (78%) of pico-cells compositions in surface layer, while in DCM layer Prochlorococcus took up 42%-98% (91%). Moreover, the maximal photochemical quantum yield (FV/FM) of Photosystem II (PS II) and the rapid light curve (RLC)-derived light utilization efficiency (α) were lower in surface than DCM layer, but the saturation irradiance (EK) was higher. In particular, we found that acutely rising temperature decreased the FV/FM and α in both surface and DCM layers, but increased the absorption cross-section (σPSII) of PS II photochemistry. Our results clearly indicate that the presently rising temperature adversely affect the photophysiology of natural phytoplankton assemblages in tropical oceans.